Risk Analysis of the Transmission Route for the African Swine Fever Virus in Mainland China - Hu, Jiang-Hong; Pei, Xin; Sun, Gui-Quan; Jin, Zhen (Frontiers in Physics, 2021)
African Swine Fever firstly broke out in mainland China in August 2018 and has caused a substantial loss to China's pig industry. Numerous investigations have confirmed that trades and movements of infected pigs and pork products, feeding pigs with contaminative swills, employees and vehicles carrying virus are the main transmission routes of ASFV in mainland China. However, which transmission route is more risky and what is the specific transmission map, still isn't clear enough. In this paper, we crawl the data related to pig farm and slaughter house from BaiDu Map by writing Python language and then construct the pig transport network. Following this, we establish ASFV transmission model over the network based on probabilistic discrete-time Markov chains. Further, we propose spatiotemporal backward detection and forward transmission algorithms in semi-directed weighted network. Through the simulation and calculation, the risk of transmission routes is analyzed, the results reveal that the infection risk for employees and vehicle with virus is the highest, followed by contaminative swills, and transportation of pigs and pork products is the lowest; the most likely transmission map is deduced, it is found that ASFV spread from northeast China to southwest China and then to west; in addition the infection risk in each province at different times is assessed, which can provide effective suggestions for the prevention and control of ASFV.